Implementation Of Management Information Systems in A State - Owned Mining Company: An Analysis of PT Antam Tbk - Rio J P Saragih; Remus Silalahi; Darwis Robinson Manalu (Fakultas Ekonomi Universitas Simalungun, 2026)
This study aims to analyze the implementation of Management Information Systems (MIS) in a state-owned mining company, with a case study of PT Aneka Tambang Tbk. The mining industry is characterized by complex operations that require integrated and accurate information to support managerial decision-making. This research adopts a qualitative descriptive approach using secondary data derived from ANTAM’s 2024 Annual Report and recent academic literature. The results indicate that Management Information Systems plays a strategic role in supporting operational efficiency, financial performance monitoring, sustainability management, and corporate governance. The findings demonstrate that Management Information Systems contributes to improved decision-making quality and organizational performance in state-owned mining enterprises. This study provides academic and practical insights into Management Information Systems implementation within capital-intensive and sustainability-driven industries. This study contributes to the literature on Management Information Systems implementation in capital-intensive state-owned enterprises by providing empirical insights from the mining industry